Pembelajaran Kontrapung dengan Menggunakan Software Sibelius di Program Studi Pendidikan Musik Fakultas Seni Pertunjukan ISI Yogyakarta - Oriana Tio Parahita Nainggolan (Institut Seni Indonesia Yogyakarta, 2018)
The terminology of counterpoint comes from the Italian language “punctus contra punctum”. Counterpoint consists of two or more melodic lines. The basic counterpoint consisting of two melodic lines (it is usually called inventions two voices). In the study of counterpoint in Music Education Study Program at Performing Arts Faculty, Indonesia Institute of the Arts Yogyakarta, the researcher found that students facing the difficulty in making inventions two voices. Regarding solve the problem, the researcher using Sibelius software as a learning media. This research is a classroom action research with the aims to increase the learning result of students in learning counterpoint by using Sibelius software. The result shows that Sibelius software can simplify and accelerate in making two-part inventions. The data obtained from students’ result in making two-part inventions and questionnaires that distribute to students at the end of the semester. In the preliminary stage, the data showed that only 6 (16, 70%) out of 36 students got excellent marks. This percentage increases until the second cycle, there are 21 (58, 33%) out of 36 students got excellent marks. This result showed the increasing of student learning outcomes in study Kontrapung II by using Sibelius software on making two-part inventions.